Lower mantle structure from paleogeographically constrained dynamic Earth models. (30th January 2013) - Bower, Dan J.; Gurnis, Michael; Seton, Maria
Abstract : [1] Seismic tomography reveals two large, low‐shear velocity provinces (LLSVPs) beneath Africa and the Pacific Ocean. These structures may have existed for several 100 Myr and are likely compositionally distinct based on observed seismic characteristics interpreted in light of geodynamic models and mineral physics constraints. We investigate the dynamics of the LLSVPs through the use of evolutionary models of thermochemical convection from 250 Ma to present day. We use a spherical convection model in which the anomalous structures have a high bulk modulus, consistent with seismic interpretation. A new progressive assimilation method incorporates constraints from paleogeography using a refined plate history model (with 1 Myr time spacing) to guide the thermal structure of the lithosphere and steer the thermal evolution of slabs in the uppermost mantle. The thermochemical structures deform and migrate along the core‐mantle boundary (CMB) through coupling to plate motions and in response to slab stresses. The models produce a ridge‐like anomaly beneath Africa and a rounded pile beneath the Pacific Ocean, which at present day agrees with tomography, waveform modeling, and other geodynamic studies. Plumes emanate from the margins of the domes and ridges of thickened boundary layer between the domes. Dense and viscous slabs can undermine the stability of high bulk modulus structures at the CMB. High bulk modulus structures are not necessarily required to satisfy dynamic constraints on the LLSVPs. Key Points: Incorporate paleogeography in thermochemical models to explore LLSVP dynamics Ridge‐like anomaly beneath Africa and a rounded pile beneath the Pacific Ocean Dense and viscous slabs compromise stability of high bulk modulus structures